Characterization of molecular structure of emulsion acrylic microgels: Exploring the Impact of molar mass on coating properties of self-crosslinkable latexes - Machotová, Jana; Zgoni, Hedvika; Podzimek, Štěpán; Stránská, E.; Puková, Kateřina (My University, 2016)
Self-crosslinkable latexes of coreshell microgel particles were synthesized by the emulsion polymerization of acrylic monomers. The molar mass of copolymers forming the shell layer was gradually reduced by isooctyl 3-mercaptopropionate included in the synthesis of the shell layers. The molar mass distribution of latex particles was determined using size exclusion chromatography and asymmetric flow field flow fractionation, respectively, both separation methods being coupled with a multi-angle light scattering detector. The results confirmed theoretical predictions and described empirically the effects of molar mass of the shell layer copolymer on decreasing the minimum film-forming temperature and influencing the end-use properties of coatings.
Charakterizace molekulární struktury emulzních akrylátových mikrogelů: studium vlivu molekulové hmotnosti na vlastnosti nátěrů tvořených samosíťujícími latexy
Keywords: Emulsion polymerization; Coreshell latex; Keto-hydrazide crosslinking; Molar mass distribution; A4F; Chain transfer; Emulzní polymerace; core-shell latex; keto-hydrazidové síťování; distribuce molekulové hmotnosti; A4F; přenos řetězce